Inflammasome-Induced Osmotic Pressure and the Mechanical Mechanisms Underlying Astrocytic Swelling and Membrane Blebbing in Pyroptosis - Zheng, Zihui; Wang, Tingting; Chen, Jiahui; Qiu, Huimin; Zhang, Chencheng; Liu, Weizhen; Qin, Simiao; Tian, Jilai; Guo, Jun (Frontiers in Immunology, 2021)
Cell swelling and membrane blebbing are characteristic of pyroptosis. In the present study, we explored the role of intracellular tension activity in the deformation of pyroptotic astrocytes. Protein nanoparticle-induced osmotic pressure (PN-OP) was found to be involved in cell swelling and membrane blebbing in pyroptotic astrocytes, and was associated closely with inflammasome production and cytoskeleton depolymerization. However, accumulation of protein nanoparticles seemed not to be absolutely required for pyroptotic permeabilization in response to cytoskeleton depolymerization. Gasdermin D activation was observed to be involved in modification of typical pyroptotic features through inflammasome-induced OP upregulation and calcium increment. Blockage of nonselective ion pores can inhibit permeabilization, but not inflammasome production and ion influx in pyroptotic astrocytes. The results suggested that the inflammasomes, as protein nanoparticles, are involved in PN-OP upregulation and control the typical features of pyroptotic astrocytes.